Influence of zinc supply on the course of infectious diarrhea in children of early age - V. V. Pechuhina; O. V. Usachova (Patologìâ)
Aim. Give a comparative characteristic of the course of infectious diarrhea in young children, residents of the Zaporizhzhia region (Ukraine), depending on their provision of zinc (Zn).